Risk and Resilience: Exploring the Ecological Factors that Impact the Recovery of Sexual Assault Survivors at Two Centres in the Western Cape - Munnik, Lucca (Department of Psychiatry and Mental Health, 2024)
Background: Sexual assault is highly prevalent in South Africa and many women who are sexually assaulted are at high risk of developing poor health outcomes, ranging from HIV to mental disorders. The high prevalence of sexual assault and the burden of poor health outcomes highlights a serious need for interventions for these women. However, it is common that survivors face many challenges when being assisted. In legal settings, there is a lack of prosecution of perpetrators and survivors often face secondary victimisation. In psychosocial settings, they have little access to counselling services with treatment being short-term and involving no follow-up procedure. These problematic legal and psychosocial barriers demonstrate a need to explore survivors' perspectives to understand what factors should be promoted to increase resilience and improve rape recovery. Aims and Objectives: This research aimed to explore how factors on Campbell et al.'s (2009) ecological model contribute to mental ill-health, resilience, and recovery in female sexual assault survivors. The ecological model explains the link between sexual assault and mental health amongst survivors. It uses factors on seven interrelated levels to examine which factors worsen or improve survivors' recovery and mental well-being. The research objectives included: 1) to explore female survivors' subjective experiences of mental health related to their sexual assault incident, 2) to explore how factors on the seven levels of the ecological model improve or worsen female survivors' mental health, and 3) to explore how factors on the ‘self-blame' level of the ecological model interact with other levels to impact female survivors' mental health. Methods: The study involved an exploratory qualitative research design using purposive sampling as the sampling method. There were 19 participants involved in the study. The data collection methods included 11 in-depth interviews with sexual assault survivors, specifically survivors of rape, and two focus group discussions with four HCWs per group. Data collection took place at two different sexual assault centres in Cape Town, Western Cape, and a framework analysis approach was used to analyse data. Results: Results were coded into themes and categorised according to the seven levels of the ecological model. The first category, the individual level, focused on the survivors' mental health experiences and coping mechanisms following sexual assault experiences. Survivors experienced a range of mental health problems, such as depression and panic attacks, and used various unhealthy and healthy coping mechanisms to cope with their mental ill-health, such as creative expression or substance use. There were also many biopsychosocial factors that either improve or worsen survivors' recovery. Biological factors include disturbed eating, sleeping and sexuality patterns, psychological factors include affected emotions, memory, and behaviour, and sociological factors included social iv support, socio-economic status, and social interactions. The second category, the assault level, found that the weapon used and triggering memories of weapons worsened reactions to trauma, and therefore recovery. Category three, the microsystem level, highlighted that negative social reactions and lack of support worsened recovery while positive family social reactions improved well-being. Category four, the mesosystem level, demonstrated that negative interactions with legal and healthcare professionals as well as poor case management impacted the way in which survivors perceived and accessed treatment. This differed to the beneficial factors which involved therapy accessed through NGOs and hearing stories from other survivors. The fifth theme, the macrosystem level, highlighted that rape misconceptions, ignorance about rape in families, and maternal history of rape played a role in hindering chances of recovery and increasing risk to mental ill-health. In contrast, raising awareness through education can help recovery progression and potentially increase support for victims. Category six, the chronosystem level, demonstrated that repetitive experiences of sexual assault have a negative impact on survivors' sense of self-worth and recovery while also worsening symptoms of mental ill-health. The final category, the self-blame level, emphasised that because survivors engaged in unhealthy coping mechanisms and internalised external blame and stigma, this led to creating and worsening feelings of guilt and shame. In contrast, attending counselling, seeking justice, talking about the rape incident, and accepting the occurrence of the assault, facilitated empowerment, well-being, and healing. Conclusion: This study aimed to explore factors that contribute to mental ill-health, resilience, and recovery in female sexual assault survivors. Findings highlighted that many different factors such as unhealthy coping mechanisms, myths about rape, and weapon use, played a role in increasing risk to mental ill-health. Conversely, factors such as therapy, social support, and empowerment increased resilience and improved recovery. Findings also revealed that self-blame was linked to all levels on the ecological model, and this hindered recovery due to survivors often blaming themselves for their rape and feeling ashamed. This research enabled survivors to share their perspectives of what factors strengthened and worsened their mental health, recovery, and resilience. By understanding which factors support or worsen rape recovery, recommendations on how to incorporate positive factors are suggested, such as educational programmes, psychosocial interventions, and further research.